The CXCR4–STAT3–IL-10 Pathway Controls the Immunoregulatory Function of Chronic Lymphocytic Leukemia and Is Modulated by Lenalidomide - Shaim, Hila; Estrov, Zeev; Harris, David; Hernandez Sanabria, Mayra; Liu, Zhiming; Ruvolo, Peter; Thompson, Phillip A.; Ferrajoli, Alessandra; Daher, May; Burger, Jan; Muftuoglu, Muharrem; Imahashi, Nobuhiko; et al. (Frontiers in Immunology, 2018)
CLL cells possess regulatory functions comparable to those of normal B10 cells, a regulatory B cell subset that suppresses effector T-cell function through STAT3-mediated IL-10 production. However, the mechanisms governing IL-10 production by CLL cells are not fully understood. Here we show that the CXCL12-CXCR4-STAT3 axis regulates IL-10 production by CLL cells and their ability to suppress T-cell effector function through an IL-10 mediated mechanism. Knockdown of STAT3 significantly impaired the ability of CLL cells to produce IL-10. Further, experiments to assess the role of lenalidomide, an immunomodulatory agent with direct antitumor effect as well as pleiotropic activity on the immune system, showed that this agent prevents a CXCL12-induced increase in p-S727-STAT3 and the IL-10 response by CLL cells. Lenalidomide also suppressed IL-10-induced Y705-STAT3 phosphorylation in healthy T-cells, thus reversing CLL-induced T-cell dysfunction. We conclude that the capacity of CLL cells to produce IL-10 is mediated by the CXCL12-CXCR4-STAT3 pathway and likely contributes to immunodeficiency in patients. Lenalidomide appears to be able to reverse CLL-induced immunosuppression through including abrogation of the CXCL12-CXCR4-S727-STAT3-mediated IL-10 response by CLL cells and prevention of IL-10-induced phosphorylation of Y705-STAT3 in T-cells.